Behaviour of exclusive breastfeeding in children of mothers with and without prior training - Pilar Maritza Almaguer Sabina; Mercedes Fonseca Hernández; Luis Alberto Corona Martínez; Carmen Guerra Cabrera; Alberto Roteta Dorado; Esteban Sánchez Martínez (Medisur)
Background: Since mankind’s onset, breast milk has been the main source of food for little children. Nevertheless, in recent years there has been an alarming trend to the decline of this practice. Objective: To determine the behaviour of exclusive breastfeeding in children of mothers with and without previous training. Methods: A community intervention, quasi-experimental, comparative and prospective study was conducted. The sample, including 160 women who had given birth in 2005 and 2006 and belonged to the Area III Polyclinic of Cienfuegos, was divided into two independent groups: one trained in breastfeeding and the other one not trained. The variables included were: age, occupation, educational level, duration of exclusive and mixed breastfeeding and introduction of artificial and complementary feeding. Results: younger mothers (42, 5%) and those who were still students are in the untrained group. The elimination of exclusive breastfeeding and the replacement of mixed feeding by artificial feeding are more precocious in the untrained mothers group (43, 8% nursed less than 2 months). The introduction of complementary breastfeeding was lower in the group of untrained mothers (23, 8% did so in 4 to 5 months). Conclusions: Training provided before or immediately after delivery is an extremely useful tool to improve quantitatively and qualitatively breastfeeding.